The Relations Between Epistimology System of Bayani, Burhani, and Irfani - Azrial Syahrur Ramadhan (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2025)
The following article tries to looking for the relations between epistemology system of bayani, burhani, and irfani. The Bayani approach is an approach which states that scientific validity depends on the closeness or similarity between text and reality. The Burhâni’s approach is made based on the process of ta’aqquli, it means reasoning thinking of abstraction to reality. Meanwhile, the irfani’s approach is based on intuition and/or spiritual experience. If these three epistemologies run alone, it will have a minimal impact even the decline of Islamic civilization itself, as has been exemplified by historiography. Departing from the above problems, looking for a relationship between the three is a way out. These three epistemologies can work together and collaborate, it will have a broad impact and have greater benefits. By integrating the three(bayani, burhani, and irfani) is the best way out that Muslims need for now.As a Muslims, we can build this civilization further by integrating the three epistemologies above.